Neutrophil adherence in chronic liver disease and fulminant hepatic failure. Issue 8 (August 1983) - Altin, M; Rajkovic, I A; Hughes, R D; Williams, R
Abstract : Abnormal adherence of neutrophils to nylon fibre in vitro was found in blood from 17 of 51 (33.3%) patients with chronic or acute liver disease of different aetiologies. Patients with chronic liver disease had a much wider range of values than the controls and the sub-group with alcoholic cirrhosis had significantly higher adherence (72.4 +/- SD 6.2%) than that of controls (65.8 +/- SD 5.2%). The patients with chronic active hepatitis (68.2 +/- 12.7%) or primary biliary cirrhosis (69.2 +/- 6.6%) were not different from controls. Significantly reduced neutrophil adherence (56.2 +/- 8.7%) was found in blood from patients with fulminant hepatic failure. These abnormalities in neutrophil adherence may be due to the effects of the split components of serum complement and dependent on the degree and duration of exposure of the neutrophils. Defects in neutrophil adherence may in part contribute to the increased susceptibility to infection in patients with acute and chronic liver disease.